Evaluation of patient care interventions and recommendations by a transitional care pharmacist - Bruce Bayley, K (Dove Medical Press, 2007)
A “transitional care pharmacist” (TCP) was deployed within an acute care setting to identify opportunities for improved continuity of care. The provision of medication reconciliation services, drug consultation, patient counseling and planning for after-hospital care was time consuming but also fruitful, resulting in roughly nine interventions per patient. Areas with the greatest potential for morbidity reduction were the resumption of home medications during the acute stay and at discharge. Allergy identification was a key contribution at admission, as was the provision of a detailed follow-up plan at discharge. Targeting high-risk patients and spreading portions of the work to other disciplines could achieve added efficiency in this service. Results have value to hospitals implementing medication reconciliation programs.